Majelis Luhur Kepercayaan Indonesia In Banyuwangi 2020-2022 - Wicaksono, Damar; Soepeno, Bambang; Nirmala Puji, Rully Putri; Triyanto, Jefri Rieski; Prasetyo, Guruh; Nasution, Ahmad Arif Budiman (JURNAL HISTORICA, 2024)
The aim of this research is to explain the process of establishing the Indonesian Supreme Trust Council organization in Banyuwangi and the impact of the founding of this organization. The method used is historical methodology which includes five stages, namely topic selection, heuristics, source criticism, interpretation and historiography. The Supreme Council of Indonesian Beliefs or commonly known as MLKI is an organization that aims to be a forum and a bridge between communities of believers in Indonesia. In general, MLKI Banyuwangi is an organization that organizes communities of believers in Banyuwangi. MLKI Banyuwangi was founded on November 20 2020 and was inaugurated by Mr. Otto Iskandar as Presidium of MLKI East Java Province. The foundation of MLKI was motivated by social conditions and regional contours. Differences in beliefs or religions as well as ethnic and cultural diversity were one of the triggers for the founding of MLKI Banyuwangi. The impact of MLKI Banyuwangi during 2020-2022 includes several points, including; assisting people who adhere to their beliefs in changing the status of religion in their population identity, providing protection for people who adhere to their beliefs in Banyuwangi, assisting the government in organizing religious events, especially traditional activities.